2010
DOI: 10.1021/jm100977d
|View full text |Cite
|
Sign up to set email alerts
|

Fruitful Adrenergic α2C-Agonism/α2A-Antagonism Combination to Prevent and Contrast Morphine Tolerance and Dependence,

Abstract: The functional in vitro study of the enantiomers of imidazolines 4-7 highlighted the role played by the nature of the ortho phenyl substituent in determining the preferred α(2C)-AR configuration. Indeed, the (S) enantiomers of 4-6 or (R) enantiomer of 7 behave as eutomers and activate this subtype as full agonists; the corresponding distomers are partial agonists. Because in clinical pain management with opioids α(2C)-AR agonists, devoid of the α(2A)-AR-mediated side effects, may represent an improvement over … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
47
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(49 citation statements)
references
References 29 publications
2
47
0
Order By: Relevance
“…These properties are in agreement with those shown by the lead 1 and its enantiomers and confirm that dual α 2C -AR agonism/α 2A -AR antagonism represents a favorable condition for inducing positive effects on morphine dependence. 9 Interestingly, such effects can even be improved by additional 5-HT 1A -R activation. Indeed, unlike clonidine, 1 or the single (S)-(+)-1 enantiomer, 2, or both its enantiomers, all behaving as α 2C -AR agonists/α 2A -AR antagonists/5-HT 1A -R agonists, alone and at the same low dose, improved morphine withdrawal syndrome and exerted a potent antidepressant-like effect.…”
Section: (S)-(+)-and (R)-(−)-2-(2-cyclopropylmethyl)propionic Acid Mementioning
confidence: 99%
See 1 more Smart Citation
“…These properties are in agreement with those shown by the lead 1 and its enantiomers and confirm that dual α 2C -AR agonism/α 2A -AR antagonism represents a favorable condition for inducing positive effects on morphine dependence. 9 Interestingly, such effects can even be improved by additional 5-HT 1A -R activation. Indeed, unlike clonidine, 1 or the single (S)-(+)-1 enantiomer, 2, or both its enantiomers, all behaving as α 2C -AR agonists/α 2A -AR antagonists/5-HT 1A -R agonists, alone and at the same low dose, improved morphine withdrawal syndrome and exerted a potent antidepressant-like effect.…”
Section: (S)-(+)-and (R)-(−)-2-(2-cyclopropylmethyl)propionic Acid Mementioning
confidence: 99%
“…9 The positive effects of 1 on dependence were also displayed by (S)-(+)-1 (potent α 2C -AR full agonist) and (R)-(−)-1 (α 2C -AR partial agonist); they both were endowed with similar α 2A -AR antagonism. 9 To confirm the aforementioned results and discover novel tools for the management of opioid withdrawal symptoms that have a major role in relapse to drug-taking behavior after detoxification, we extended the study to the recently reported allyphenyline analogue 2, 7 now named cyclomethyline, and its enantiomers, prepared in the present investigation. Compound 2 showed interesting α 2C -AR agonism/α 2A -AR antagonism (Table 1), and according to what reported for 1, 7 this functional profile might be associated with a preferred extended molecular conformation.…”
mentioning
confidence: 98%
“…In the recent years allyphenyline, a novel α2-AR ligand endowed with peculiar pharmacological profile has been synthetized and characterized [22][23][24]. Among the three α2-AR subtypes allyphenyline behaves as an agonist only at the α2C-AR subtype, while it does not bind to α2B-ARs and behaves as a neutral antagonist at the α2A-AR subtype in vitro [22].…”
Section: Introductionmentioning
confidence: 99%
“…1,6,7 Therefore, since prolonged abstinence remains a major challenge, strategies addressed to discover multifunctional agents that ameliorate withdrawal symptoms and relieve depressive disorders should be explored. Recently, 8,9 we reported that allyphenyline (1) and cyclomethyline (2) (Chart 1), devoid of sedative side effects, were able at the same low dose (0.05 mg/kg) to significantly decrease the naloxone-precipitated withdrawal syndrome and to exert a …”
mentioning
confidence: 99%
“…19 On the basis of the interesting results obtained with 1 and 2, the aim of the present study was to widen the availability of tools potentially useful in managing opioid addiction and associated disorders. To this end, we first determined the 5-HT 1A -R profiles of 3 and its enantiomers, 8 and 4−6. 15 The choice of such compounds was suggested by the observation that, analogously to 1 and 2, they were endowed with efficacious α 2C -AR agonism/α 2A -AR antagonism due to their preferred extended conformation.…”
mentioning
confidence: 99%